On the A1(1) reduction of the two-component KP hierarchy - Jaulent, Marcel; Manna, Miguel A.; Martinez Alonso, Luis; Medina Reus, Elena (Elsevier, 1990)
The reduction of the two-component KP hierarchy with respect to the affine Lie algebra A1(1) is found to be equivalent to the hierarchy of integrable systems associated with an energy-dependent Schrödinger operator. The classical Boussinesq system turns out to be the reduction of a recently introduced (2 + 1)-dimensional integrable model. © 1990.